أصول الدوحة و قطر البيوت الثراثية القطرية - حزمة المدرّس - Mariam Al Thani (16020516) (2023)
This item is a Teacher Guide and Notes produced by UCL Qatar as part of the The Origins of Doha and Qatar Project, and is part of Origins of Doha and Qatar: Traditional Qatari Homes School Pack - Arabic collection.